2020
DOI: 10.3390/en13215583
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cyber Attacks on AC and High-Voltage DC Interconnected Power Systems with Emulated Inertia

Abstract: The high penetration of renewable energy resources and power electronic-based components has led to a low-inertia power grid which would bring challenges to system operations. The new model of load frequency control (LFC) must be able to handle the modern scenario where controlled areas are interconnected by parallel AC/HVDC links and storage devices are added to provide virtual inertia. Notably, vulnerabilities within the communication channels for wide-area data exchange in LFC loops may make them exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…An attacker can use a variety of tactics to initiate DoS attacks. For instance, the attacker can saturate the network with traffic, target the routing protocols, infiltrate devices and stop them from providing data, and jam the communication channels [ 10 ].…”
Section: Cyber Physical System Threat Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…An attacker can use a variety of tactics to initiate DoS attacks. For instance, the attacker can saturate the network with traffic, target the routing protocols, infiltrate devices and stop them from providing data, and jam the communication channels [ 10 ].…”
Section: Cyber Physical System Threat Modelingmentioning
confidence: 99%
“…Recent investigations have shown that if a certain number of sensor nodes are hacked, conventional authentication measures cannot stop an FDI attack. In this study [ 10 ], a mathematical equation was used to describe a characteristic of grid parameters during an FDI attack, especially at specific times.…”
Section: Cyber Physical System Threat Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Misuse of communication systems may bring extra challenges. Cyber attacks may attempt to exploit system vulnerabilities (Pan et al, 2020). Understanding modes of attack and system vulnerabilities potentially leading to blackouts allows to design simulation frameworks to analyze impacts and to protect against such attacks (Rajkumar et al, 2020).…”
Section: Research Focusmentioning
confidence: 99%